2014
DOI: 10.3109/08820538.2014.962175
|View full text |Cite
|
Sign up to set email alerts
|

Poppers Maculopathy: Complete Restitution of Macular Changes in OCT after Drug Abstinence

Abstract: Toxic maculopathy due to the consumption of poppers is an important differential diagnosis in acute visual loss without clinico-morphological correlate. Optical coherence tomography is the only reliable diagnostic tool in these cases. Complete recovery of visual function and macular morphology is rare, even after cessation of drug abuse. Oral lutein therapy may have a beneficial effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
3
11
0
4
Order By: Relevance
“…Moreover, our study shows that vitelliform-like lesions tend to occur amongst chronic users and that a significant proportion of them had not improved over time despite drug cessation. The effect of prolonged poppers consumption has already been highlighted in several studies but the conclusions on the visual prognosis are contradictory [3,4,5]. Our study brings further confirmation that chronic use may be associated with more severe and permanent photoreceptor damage.…”
supporting
confidence: 76%
“…Moreover, our study shows that vitelliform-like lesions tend to occur amongst chronic users and that a significant proportion of them had not improved over time despite drug cessation. The effect of prolonged poppers consumption has already been highlighted in several studies but the conclusions on the visual prognosis are contradictory [3,4,5]. Our study brings further confirmation that chronic use may be associated with more severe and permanent photoreceptor damage.…”
supporting
confidence: 76%
“…This supports previous findings; a patient with a 12-year history of poppers use demonstrated complete restitution on OCT 6 months after cessation 18. One of the few exceptions to this was a case who had used poppers regularly for years and who showed no improvement at 3 months, objective or subjective, following cessation 12.…”
Section: Discussionsupporting
confidence: 89%
“…Patients had better visual recovery if they abstained from the drug once symptoms began, or if they were taking the drug infrequently or for the first time [4,9]. Pahlitzsch et al [10] described one patient who demonstrated near resolution of the maculopathy following 6 months of oral lutein supplementation. The time needed for full visual rehabilitation is highly variable, ranging from a period of 6 months to over 3 years.8 Patients should be advised that the long-term prognosis of this disease remains largely uncertain.…”
Section: Discussionmentioning
confidence: 99%